2010
DOI: 10.1185/03007995.2010.495564
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal ketorolac for acute postoperative pain

Abstract: Intranasal ketorolac was well tolerated and provided effective pain relief within 20 minutes with reduced opioid analgesia use. While IN ketorolac was assessed in an inpatient, conventional surgery setting in this study, IN ketorolac use may have more relevance for use in outpatient settings and ambulatory surgery or fast-track surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 23 publications
2
26
0
3
Order By: Relevance
“…Ketorolac absorbed through the nasal mucosa was well tolerated and an analgesic effect was achieved within 20 min, without the side effects of morphine-like painkillers. Ketorolac relieves pain through inhibition of arachidonic acid synthesis at the level of cyclooxygenase and has no central opioid effects, making it relatively safe for clinical use [21]. In this study, none of the 95 patients treated with 5% ketorolac tromethamine had any drug allergies or other adverse drug reactions.…”
Section: Discussionmentioning
confidence: 83%
“…Ketorolac absorbed through the nasal mucosa was well tolerated and an analgesic effect was achieved within 20 min, without the side effects of morphine-like painkillers. Ketorolac relieves pain through inhibition of arachidonic acid synthesis at the level of cyclooxygenase and has no central opioid effects, making it relatively safe for clinical use [21]. In this study, none of the 95 patients treated with 5% ketorolac tromethamine had any drug allergies or other adverse drug reactions.…”
Section: Discussionmentioning
confidence: 83%
“…To date, there are a total of five published studies reporting the efficacy and safety of IN ketorolac. Three studies consisted of patients who underwent major surgery (eg, hysterectomies, hip replacements, and abdominal surgeries), one study consisted of patients who underwent major dental surgery (eg, third molar extraction surgery), and phase 1 study in healthy patients assessed the pharmacokinetics and safety . Summary of major surgery studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…17 A randomized controlled trial in patients after abdominal surgery showed 26% less morphine consumed in the first 48 hours postoperative. 18 Both studies remarked on the rapid onset of analgesia, which lasted up to 8 hours, 17 and suggested its benefit in ambulatory or fast-track surgery. 18 The rapid onset and improved analgesia seen with IN ketorolac may be due to higher penetration via the cribriform plate and into the cerebrospinal fluid.…”
Section: Nsaidsmentioning
confidence: 98%
“…18 Both studies remarked on the rapid onset of analgesia, which lasted up to 8 hours, 17 and suggested its benefit in ambulatory or fast-track surgery. 18 The rapid onset and improved analgesia seen with IN ketorolac may be due to higher penetration via the cribriform plate and into the cerebrospinal fluid. Higher cerebrospinal fluid levels of NSAIDs have been associated with greater analgesia.…”
Section: Nsaidsmentioning
confidence: 98%